Guidelines for grit sampling and characterization. (Water Environment Federation, 2016)
Annotation Guidelines for Grit Sampling and Characterization addresses the "last frontier" in liquid systems treatment by documenting and examining the methods currently in use. Driven by the industry's increasing need to determine how grit can be better characterized, modeled, and reliably removed, this book is a first step toward understanding the implications of the methods selected and allowing for proper design and optimization of grit removal systems. The book discusses methods for:characterizing grit;obtaining a grit sample, includingcross-channel sampling and dry sieving, full-depth sampling and wet sieving, andprimary sludge sampling;analyzing a grit sample; andusing grit characterization data. The authors also identify gaps in the current knowledge and make the case for further research in critical areas
"WEF Special Publication."
"Prepared by the Grit Sampling and Characterization Task Force of the Water Environment Federation."--Page iii
Keywords: Sewage -- Sampling -- Guidebooks.; Sewage -- Purification -- Guidebooks.; Sewage disposal plants -- Guidebooks.; Sedimentation and deposition.; elektronické knihy; electronic books